Make no exception, save one: American exceptionalism, the American presidency, and the age of Obama. Issue 4 (1st October 2016) - Gilmore, Jason; Sheets, Penelope; Rowling, Charles
ABSTRACT: This paper explores the circumstances under which U.S. presidents have invoked American exceptionalism in major speeches and how this concept has culminated in the Obama presidency. We find that U.S. presidents have increased their invocations of American exceptionalism since the Second World War and that they have relied heavily on this concept in times of national crises. Moreover, we demonstrate the overwhelming propensity of President Obama, relative to his predecessors, to emphasize American exceptionalism. We argue that this is due to the double-crisis nature of his presidency – two major wars and a recession – in addition to the racial bind that he has endured throughout his presidency. We reflect on the implications for other minority politicians and the broader American public.